(untitled) (Majalah Kedokteran Bandung, 2019)
The use of non-human primate (NHP) animal models, which anatomical and physiological similarities to human, is important for the sake of learning the anatomical properties. This study aimed to characterize the cranial, maxillofacial, and skull base structures of non-human primates as a potential model suitable for a cranial craniotomy model. Adult Macaca fascicularis (MF) skulls classified asspecificpathogen-free for TB, SIV, SV40, Polio, Foamy virus and Herpes B virus from PT Bio Farma (Persero) Animal Lab. Library were used to represent the anatomical model.The open access database from Mammalian Crania Photographic Archive 2nd Edition (MCPA2) was used for cranial characterization analysis. This study was performed at the Department of Neurosurgery, Dr. Hasan Sadikin General Hospital and the Animal Laboratory of PT. Biofarma (Persero) from November 2018 to January 2019. The skull base structures were assessed for its analogies with its human counterpart. Comparison by t-student analysis between male and female skulls shows the mean male cranial length (CL) is greater than in female (116.68 vs 102.50 mm), with p=0.000; the mean male bizygomatic width (BZB) is greater than in female (79.30 vs 69.70 mm) with p=0.001; the mean male posterior cranial breadth (CBN) is greater than in female (63.40 vs 58.79 mm) with p=0.019; and the mean male cranial base length (CBL) is greater than in female (63.32 vs 57.55 mm), with p=0.001. The skull of MF is suitable for Neurosurgery and Neuroscience study since the MF cranial characterization and structure are similar to that of human. Its structure is ideal for performing craniotomy since it has several characteristics such as cranial vault, maxillofacial structure with huge temporal muscle, and skull base structure. Karakteristik Kranium, Maksilofasial, dan Struktur Dasar Tengkorak Non-human Primate Macaca fascicularis dewasa: Studi Pendahuluan untuk Model Craiotomi Kranium Penggunaan hewan model berasal dari primata bukan-manusia (NHP), dimana secara anatomis dan fisiologis mirip dengan manusia, sangat penting untuk dapat mempelajari struktur anatominya. Penelitian ini bertujuan untuk karakterisasi struktur kranium, maksilofasial dan dasar tengkorak primata (Non-human Primate) yang berpotensi sebagai model penelitian kraniotomi. Tengkorak dewasa Macaca fascicularis (MF) dari Laboratorium Hewan PT Biofarma (Persero), bebas infeksi TBC, SIV, SV40, Polio, Foamy Virus, dan Herpes B digunakan sebagai model anatomi. Basis data terbuka Mammalian Cranial Photographic Archive 2nd Edition (MCPA2) digunakan untuk analisis kranium. Penelitian dilakukan di Departmen Bedah Saraf RSHS dan Laboratorium Hewan PT. Biofarma pada November 2018–Januari 2019. Struktur tengkorak MF dipelajari analogi seperti pada struktur tengkorak manusia. Analisis uji-t tengkorak jantan dan betina menunjukan rerata panjang kranial (Cranial length, CL) jantan lebih panjang dibanding betina (116.68 vs 102.50 mm, p=0.000); rerata bizygomatic width (BZB) jantan lebih panjang dibanding betina (79.30 vs 69.70 mm, p=0.001); rerata posterior cranial breadth (CBN) jantan lebih panjang dibanding betina (63.40 vs 58.79 mm, p=0.019);dan rerata cranial base length (CBL) jantan lebih panjang dibanding betina (63.32 vs57.55 mm, p=0.001). Tengkorak MF sesuai untuk berbagai penelitian bidang bedah saraf dan neurosains. Karakterisasi kranial dan strukturnya sama dengan yang dimiliki manusia. Struktur kranium MF merupakan model ideal untuk kraniotomi berdasar karakteristik tulang tengkorak, otot temporal besar pada maksilofasial, dan struktur dasar tengkorak.